2018
DOI: 10.1186/s40066-018-0229-6
|View full text |Cite
|
Sign up to set email alerts
|

Climate change and potential impacts on agriculture in Bhutan: a discussion of pertinent issues

Abstract: Background: The Himalayan country of Bhutan is typically an agrarian country with about 57% of the people depending on agriculture. However, farming has been constrained by the mountainous topography and rapid changes in environmental variabilities. With climate change, agricultural production and food security is likely to face one of the biggest challenges of the twenty-first century. The country has already been experiencing some impacts of climate change, such as crop loss to unusual outbreaks of diseases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
50
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(51 citation statements)
references
References 31 publications
0
50
0
1
Order By: Relevance
“…In Bhutan, Kalra et al (2007) Bangladesh < 3 °C Yield loss about 60% 1Yield decrease by 2.6-13.5% 21 Karim et al (1996); 2 Basak et al (2009) > 3 °C Yield loss exceed 60% 1Yield decrease by 0.11-28.7%) 2 1 Karim et al (1996); 2 Basak et al though farming is constrained by the mountainous topography, almost 57% of the people depend on agriculture. The country has been experiencing the impacts of climate change such as crop loss to unusual outbreaks of diseases and pests, erratic rainfalls, windstorms, hailstorms, droughts, flash floods, and landslides (Chhogyel and Kumar 2018). A similar level of yield reduction was also reported in Bangladesh, Pakistan, and Sri Lanka (Table 1).…”
Section: Impact Of Climate Change On Agriculture In South Asiamentioning
confidence: 59%
“…In Bhutan, Kalra et al (2007) Bangladesh < 3 °C Yield loss about 60% 1Yield decrease by 2.6-13.5% 21 Karim et al (1996); 2 Basak et al (2009) > 3 °C Yield loss exceed 60% 1Yield decrease by 0.11-28.7%) 2 1 Karim et al (1996); 2 Basak et al though farming is constrained by the mountainous topography, almost 57% of the people depend on agriculture. The country has been experiencing the impacts of climate change such as crop loss to unusual outbreaks of diseases and pests, erratic rainfalls, windstorms, hailstorms, droughts, flash floods, and landslides (Chhogyel and Kumar 2018). A similar level of yield reduction was also reported in Bangladesh, Pakistan, and Sri Lanka (Table 1).…”
Section: Impact Of Climate Change On Agriculture In South Asiamentioning
confidence: 59%
“…This highlights the need for climate smart suitable policies in agriculture development. It has been reported that the rice sector in Bhutan is already experiencing challenges of massive land fallowing due to various reasons, including climate change impacts (DoA, 2016;Chhogyel and Kumar, 2018). Even from the biodiversity point of view, rice ecosystems are one of the most important ecological entities that provide ecological services through nutrient cycling and support to large agrobiodiversity (Settele et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…This highlights the need for climate smart suitable policies in agriculture development. It has been reported that the rice sector in Bhutan is already experiencing challenges of massive land fallowing due to various reasons, including climate change impacts (DoA, 2016; Chhogyel and Kumar, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, the impacts of climate shock on households will be felt most in developing countries already facing development challenges [1][2][3][4]. The poorest countries are the most exposed to the impacts of natural disasters (cyclones, tsunamis, floods, drought, land erosion, etc.).…”
Section: Introductionmentioning
confidence: 99%